Use of 2-alkenyl-3-(chloromethyl)oxiranes in the synthesis of 1,5-dien-3-ols - Servi, S; Ahmedzade, M; Çoskun, M; Cansiz, A (Bureau Scientific Publ, 2000)
The reaction of unsaturated chloromethyl oxiranes with magnesium in tetrahydrofuran or with metallic sodium in methanol leads to the corresponding 1,5-dien-3-ols.
Keywords: Unsaturated Carbonyl-Compounds; bis-Allylic Ethers; Sigmatropic Sequences; <2,3>-Wittig Rearrangement